Dezocine modulates the reinstatement of conditioned place preference in morphine-dependent rats via the dopamine reward circuitry - He, Yan; Piao, Zhi-Sheng; Jia, Yi; Wu, Hui-Qi; Wang, Xiao-Qiang; Yu, Wei-Feng; Wu, Fei-Xiang (Frontiers in Neuroscience, 2025)
IntroductionOpioid addiction is a significant public health issue, with existing treatments such as buprenorphine and methadone exhibiting limitations, including side effects and insufficient prevention of relapse. Novel therapeutic strategies are needed to address these challenges. This study investigates the potential of dezocine in reducing addiction-related behaviors and preventing relapse.MethodsA morphine-induced conditioned place preference (CPP) model was established in rats to evaluate the effect of dezocine on addiction-related behaviors. Behavioral assessments were conducted to measure withdrawal symptoms and CPP reinstatement. To explore the underlying mechanism, Western blot (WB) and immunofluorescence (IF) were used to quantify the expression of phosphorylated DARPP32 (p-DARPP32) and DOPA decarboxylase (DDC) in reward-related brain regions, including the nucleus accumbens (NAc), ventral tegmental area (VTA), hippocampus (HP), and prefrontal cortex (PFC).ResultsDezocine significantly reduced withdrawal symptoms and prevented CPP reinstatement, indicating its potential to alleviate addiction behaviors. Western blotting and immunofluorescence analysis revealed that dezocine increased p-DARPP32 expression in the NAc, VTA, HP, and PFC, without altering DDC levels.DiscussionThese findings suggest that dezocine may exert its therapeutic effects by inhibiting kappa opioid receptor activation and enhancing dopamine signaling in reward-related brain circuitry. The increase in p-DARPP32 expression in key brain regions supports this mechanism, providing insights into the potential clinical application of dezocine for managing opioid addiction. Dezocine represents a promising candidate for opioid addiction treatment, with the ability to control withdrawal symptoms and prevent relapse.